Cote d'Ivoire : Technical Assistance Report. (IMF Staff Country Reports; Country Report ;, 2014)
This Technical Assistance Report outlines that despite the lack of a suitable legal and regulatory framework, Cote d'Ivoire has made significant progress in its preparations for implementing the new budgeting tools required in the West African Economic and Monetary Union Harmonized Public Financial Framework. The macroeconomic framework and medium-term fiscal framework efforts are being implemented normally. In view of the current state of the overall process, the mission considers it reasonable to plan to have FY2020 as the first operational year for the program budget to replace the current line item budget, subject to effectively implementing the various reforms and measures.